Long-term successfull treatment of patient with history of Systemic Lupus Erythematosus complicated with Acute Myocarditis and Dilated Cardiomyopathy - case report - Mateusz Ziomek; Aleksandra Bożym; Paulina Lis; Wojciech Kaźmierski; Jakub Jurek; Anna Ziobro; Alicja Kamińska; Jakub Kozłowski; Bartłomiej Żaczek (Kazimierz Wielki University, 2024)
Introduction and aim. Systemic lupus erythematosus (SLE) is a chronic, autoimmune disorder that may affect every organ. The use of immunosuppression has changed a natural course of the disease. Thereupon mortality in SLE is not only associated with implications of disease activity and its impact on cardiovascular system but also with treatment-related complications like cytopenia or increased risk of infection, which can lead to a life-threatening sepsis. Description of the case. We present a case of a 60-year-old Caucasian female patient with a long-time history of active SLE, who has first developed nephrotic syndrome and then acute lupus myocarditis (LM) complicated by dilated cardiomyopathy. Conclusion: The appearance of LM and its complications seem to be a landmark event in the further course of disease.